Compadre Colonialism Studies in the Philippines under American Rule - Owen, Norman G. (Michigan Papers On South And Southeast Asia, 2020)
This volume is a manifestation of the continuing interest of scholars at the University of Michigan in Philippine studies. Written by a generation of post-colonial scholars, it attempts to unravel some of the historical problems of the colonial era. Again and again the authors focus on the relationship of the ilustrados and the Americans, on the problems of continuity and discontinuity, and on the meaning of "modernization" in the Philippine context. As part of the Vietnam generation, these authors have looked at American imperialism with a new perspective, and yet their analysis is tempered, not strident, and reflective, not dogmatic. Perhaps the most central theme to emerge is the depth of the contradiction inherent in the American colonial experiment. [vi-vii]